The impact of the COVID-19 pandemic on chlamydia infection in South Korea: a comparison between the pre-pandemic and during-pandemic periods - Chiara, Achangwa; Ryu, Sukhyun; Jung, Jae-Heon; Hwang, Se-Min (Frontiers in Public Health, 2023)
Background Prior to COVID-19 pandemic, a yearly upward trajectory in the number of chlamydia infection cases was observed in South Korea. However, in response to the COVID-19 pandemic, Korea implemented several public health and social measures, which were shown to have an impact on the epidemiology of other infectious diseases. This study aimed to estimate the impact of the COVID-19 pandemic on the incidence and number of reported chlamydia infections in South Korea. Methods Using the monthly number of reported chlamydia infection data between 2017 and 2022, we compared the trends in the reported numbers, and the incidence rates (IR) of chlamydia infection stratified by demographic characteristics (sex, age group, and region) in the pre- and during COVID-19 pandemic period (January 2017–December 2019 and January 2020–December 2022). Results We observed an irregular downward trajectory in the number of chlamydia infection in the during-pandemic period. A 30% decrease in the total number of chlamydia infection was estimated in the during-pandemic compared to the pre-pandemic period, with the decrease greater among males (35%) than females (25%). In addition, there was a decrease in the cumulative incidence rate of the during COVID-19 pandemic period (IR: 0.43; 95% CI: 0.42–0.44) compared to the pre-pandemic period (IR: 0.60; 95% CI: 0.59–0.61). Conclusions We identified decrease in the number of chlamydia infection during COVID-19 pandemic which is likely due to underdiagnosis and underreporting for the infection. Therefore, strengthening surveillance for sexually transmitted infections including chlamydia is warranted for an effective and timely response in case of an unexpected rebound in the number of the infections.